Formulation, Evaluation and Optimization of Pectin- Bora Rice Beads for Colon Targeted Drug Delivery System - Kuldeep Hemraj Ramteke; Lilakant Nath (Tabriz University of Medical Sciences, 2014)
Purpose: The purpose of this research was to established new polysaccharide for the colon targeted drug delivery system, its formulation and in vitro and in vivo evaluation. Methods: Microspheres containing pectin and bora rice were prepared by ionotropic gelation technique using zinc acetate as cross linking agent and model drug used was glipizide. A 32 full factorial design was employed to study the effect of independent variables, polymer to drug ratio (A), and concentration of cross linking agent (B) on dependent variables, particle size, swelling index, drug entrapment efficiency and percentage drug release. Results: Results of trial batches indicated that polymer to drug ratio and concentration of cross linking agent affects characteristics of beads. Beads were discrete, spherical and free flowing. Beads exhibited small particle size and showed higher percentage of drug entrapment efficiency. The optimized batch P2 exhibited satisfactory drug entrapment efficiency 68% and drug release was also controlled for more than 24 hours. The polymer to drug ratio had a more significant effect on the dependent variables. In vivo gamma scintigraphy study of optimized pectin-bora rice beads demonstrated degradation of beads whenever they reached to the colon. Conclusion: Bora rice is potential polysaccharide for colon targeted drug delivery system.